Adapt and Adopt: A Reflective Account of Strategies and Practices in an Extensive Reading Course - Murtiana, Rahmila (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Extensive Reading (ER) is an approach that encourages learners to read a large amount of self-selected material in the target language. While ER has proven effective in supporting foreign language acquisition, its implementation often faces challenges such as students' low motivation, limited vocabulary, and restricted access to English books or authentic reading materials. Against this backdrop, I present a reflective account of my experience in addressing these challenges while teaching an ER course. Grounded in my belief that teachers should continuously engage in meaningful practices beyond routine procedures, I implemented several strategies and made some adaptation in my ER class. The strategies included adopting reading materials from free online resources, using reading logs to track progress, and assigning the students to create an infographic to summarise and visualise their reading. Employing an autoethnographic approach, I reflect on the teaching and learning process throughout the semester, the students’ engagement with the tasks, and how my instructional decisions were shaped by ongoing analysis of their work. This reflective account offers insights that may benefit other teachers seeking to enhance their instruction and implement adaptive approaches in their ER courses.